Macaranga hullettii King ex Hook.f : SOURCE OF FLAVONOIDS - Pramana, Aditiya Hadi Ryan; Marliana, Eva; Ruga, Ritbey (Jurusan Kimia FMIPA UNMUL, 2020)
Flavonoid compound had been isolated and characterized on fraction ethyl acetate of Macaranga hullettii King ex Hook.f leaves. The separation process in fraction ethyl acetate was performed using vacuum and gravity column chromatography with a gradient polarity method. The isolate was characterized as MH-1 flavonoid compound in the yellow crystals and 0.0432 g. Analysis of MH-1 with spectrophotometer UV showed two peaks at Î» 268.46 (band II) and 340 nm (band I). Analysis of MH-1 with spectrophotometer IR showed OH functional groups, C-O-C, C=O, aliphatic C-H, aromatic C-H, and aromatic C=C. The MH-1 is assumed to be a flavonoid.